2021
DOI: 10.3390/jintelligence10010001
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Differential Role of General and Specific Processing Speed in Predicting Mathematical Achievement in Junior High School

Abstract: Processing speed is divided into general (including perceptual speed and decision speed) and specific processing speed (including reading fluency and arithmetic fluency). Despite several study findings reporting the association between processing speed and children’s mathematical achievement, it is still unclear whether general or specific processing speed differentially predicts mathematical achievement. The current study aimed to examine the role of general and specific processing speed in predicting mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(81 reference statements)
2
2
0
Order By: Relevance
“…These ndings add support for the important role of PS in learning particularly academic uency [21,24,36,40]. Only Coding (graphomotorcognitive PS) was found to be a signi cant predictor for MF in children with ADHD, which is consistent with the results of the study done by Jacobson et al [26] in children with sluggish cognitive tempo symptoms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These ndings add support for the important role of PS in learning particularly academic uency [21,24,36,40]. Only Coding (graphomotorcognitive PS) was found to be a signi cant predictor for MF in children with ADHD, which is consistent with the results of the study done by Jacobson et al [26] in children with sluggish cognitive tempo symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…For examples, the Stop-signal task or the Go/no-go task were commonly used to measure motor PS in young children [19]; the Symbol Search subtest of the Wechsler Intelligence Scale for Children, 4th edition (WISC-IV) was employed to measure children's perceptual PS [20]; and the Coding/Coding Copying subtests of the WISC-IV were used to measure children's graphomotor-cognitive PS [16]. In addition to these three types (i.e., motor, perceptual, and graphomotor-cognitive) of PS, other studies also classi ed PS into general (including perceptual PS and decision PS) and speci c (including reading and arithmetic uency) processing speed [21].…”
Section: Introductionmentioning
confidence: 99%
“…Results of the second objective revealed that MF was significantly correlated with perceptual, cognitive, and verbal PS, suggesting lower MF performance in children with ADHD was related to their PS deficits. These findings further supported the importance of PS (a basic skill rather than an executive function) in learning, particularly academic fluency (Cheng et al, 2022;Cui et al, 2017;Formoso et al, 2018;Koponen et al, 2017). Among the various types of PS, only Coding (cognitive PS) was a significant predictor for MF in children with ADHD; this finding was consistent with the results found in children with sluggish cognitive tempo symptoms (Jacobson & Mahone, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…The study utilizes machine learning to assess soil fertility degradation in a coal eld, providing insights into the impact of coal mining activities on soil health and fertility [15].…”
Section: The Study Compared Extreme Learning Machine (Elm) With Multi...mentioning
confidence: 99%